Case report: Aggressive NSCLC with partial BRG-1 deficiency and KRAS G12C mutation: a case study and treatment challenges - Jin, Chengwei; Ge, Hong; Hou, Dongsheng; Li, Jing; Tan, Mingming (Frontiers in Oncology, 2024)
BackgroundSMARCA4-deficient (BRG-1 deficient) primary thoracic tumors are rare aggressive malignancies associated with poor prognosis. While complete BRG-1 loss is well-documented, the clinical implications of partial BRG-1 deficiency remain unclear. This case report explores a case of mixed lung cancer with partial BRG-1 deficiency and KRAS G12C mutation, highlighting its clinical relevance, treatment challenges, and the importance of comprehensive molecular profiling.MethodsWe performed immunohistochemistry, next-generation sequencing, and PD-L1 expression analysis to characterize the tumor. Treatment included surgical resection, chemotherapy, and immunotherapy.Case presentationWe present a case of early-stage mixed lung cancer with partial BRG-1 deficiency in a 66-year-old male, treated with surgical resection, chemotherapy, and later, a PD-1 inhibitor. Despite aggressive treatment, rapid progression to brain metastasis was observed, underscoring the need for tailored approaches.ConclusionPartial BRG-1 deficiency may lead to aggressive clinical behavior, similar to complete BRG-1 loss. This case emphasizes the importance of comprehensive molecular profiling to guide treatment decisions and suggests further investigation into combined therapeutic strategies, including immunotherapy.